The paths of utopia: approaches and perspectives from the field of social economy - Rosa, Paula Cecilia (Cooperativismo & Desarrollo, 2016)
Purpose: This article is an introduction to the study of the social economy, providing a first approach to the main schools of thought, debates, and approaches found in various studies conducted in this area. Topics: It begins with a synthetic characterization of the schools of thought that gave rise to the social economy,the particularities of the social subjects that compose it, and the contrasts found in different territorial contexts. Moreover, its transformations are discussed in relation to the “social question” in order to arrive at its current situation. Development: In this article, the main discussions will be presented from the analyticalcategory of field. This was constructed to refer to the social economy as a branch of specific knowledge that has its own object of study, theoretical corpus, and particular research methodology; however, it is also conceived as a complex social and political reality consisting of experiences, practices, and actors of differenttypes (State, producers, organizations, cooperatives, etc.). Conclusions: The termfield is used and defined in this article to account for the complexity of the social economy based on the variety of forms it can take.
Keywords: social question; social economy; neoliberalism; utopian socialists